The Dilemma between Environment and Economy: Combatting the Challenges of Illicit Drugs in Laos - Muhammad Ismail Ash Shiddiq; Regina Farah Nafilah (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2022)
This research aims to analyze 1) the Lao government’s responses in coping with illicit drugs in Laos; 2) the responses of IGO, particularly UNODC, in addressing the illicit drugs issue in Laos; (3) the impacts of opium farming on the economy and environment in Laos. The results of this research reveal that the Lao government is very committed to dealing with the illicit drugs issue, reflected by its involvement in international conventions and long-term national planning. However, these steps could not achieve maximum results as many former opium farmers in Laos could not find sustainable jobs, thus at risk of reverting to opium farming. Meanwhile, as IGO, UNODC played an essential role in assisting the Lao government in eliminating opium farming and creating sustainable jobs. The cooperation between UNODC and the Lao government improved the opium farming situation in Laos. However, the concern for the environment caused by opium farming has not been found, even though illegal opium farming causes deforestation, decreased biodiversity, and soil erosion.